Vagones exclusivos para mujeres en sistemas de metro: entre percepción de seguridad y límites estructurales. Evidencia internacional y reflexiones para Lima - Córdova Chavez, Lucia Salome (Pontificia Universidad Católica del Perú, 2025)
This article analyzes gender-segregated spaces in metro systems as a response to sexual harassment in public transport. Based on a comparative study structured across five dimensions (operational design, governance and enforcement, complementary measures, reported outcomes, and controversies), it reviews five international cases (Mexico City, Tokyo, Dubai, Cairo, and Rio de Janeiro) together with a baseline analysis for Lima, with the aim of identifying achievements, limitations, and transferability conditions. The findings show that women-only cars consistently increase users perceived safety and comfort, and, in high-demand contexts, may support longer and more continuous trips. However, their structural effectiveness is limited: harassment persists in micro-spaces of the journey (station entrances, platforms, transfer corridors), reporting rates remain low, and suboptimal operational design (number of cars, service hours and coverage) can overcrowd mixed cars or displace violence. Moreover, social acceptance and compliance depend on the institutional capacity to enforce and sustain complementary measures. For Lima, the article proposes implementing evaluable peak-hour pilots, coupled with a clear sanctioning regime, reinforced surveillance, improved station access, and co-responsibility campaigns, along with rigorous impact assessments to determine the measure’s viability before any potential scale-up.

Este artículo analiza la separación espacial por género en sistemas de metro, como respuesta al acoso sexual en el transporte público. Con base en un estudio comparativo estructurado en cinco dimensiones (diseño operacional, gobernanza y fiscalización, medidas complementarias, resultados reportados y controversias), se revisan cinco casos internacionales (Ciudad de México, Tokio, Dubái, El Cairo y Río de Janeiro), junto con una línea base para Lima, con el fin de identificar logros, límites y condiciones de transferibilidad. Los resultados muestran que los espacios exclusivos incrementan consistentemente la percepción de seguridad y la comodidad de las usuarias, y, en contextos de alta demanda, pueden favorecer recorridos más largos. Sin embargo, su efectividad estructural es acotada: el acoso persiste en microespacios del viaje (accesos, andenes, pasillos de transbordo), las denuncias se mantienen bajas, y un diseño operativo insuficiente (número de vagones, horarios, cobertura) puede saturar los vagones mixtos o desplazar la violencia. Además, su aceptación social y su cumplimiento dependen de la capacidad institucional para fiscalizar y sostener medidas complementarias. Para Lima, se propone implementar pilotos evaluables en hora punta, articulados con un régimen sancionador claro, vigilancia reforzada, mejoras en accesos y campañas de corresponsabilidad, junto con mediciones rigurosas de impacto que determinen su viabilidad antes de cualquier escalamiento.
Women-only carriages in metro systems: between perceived safety and structural limitations. International evidence and Lessons for Lima
Keywords: Public Transport; Gender; Sexual Harassment; Spatial Segregation; Lima; Transporte público; Género; Acoso sexual; Segregación espacial; Lima; https://purl.org/pe-repo/ocde/ford#5.07.00